2010
DOI: 10.1007/s11060-010-0498-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain tumor patients’ views on deception: a qualitative study

Abstract: Given the trust the public places in the medical profession, the question of when it might be acceptable to minimally deceive patients, in their best interests, is a challenging one to answer. In this study, we explore neuro-oncology patients' attitudes towards dilemmas in which they may feel deceived, and with that information make recommendations on what steps physicians can take to avoid breaking that trust. Qualitative case study methodology was used. Thirty-two face-to-face interviews with post-operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In the end the most important thing is that patients are given information necessary to assess therapy options and make informed consent, for example, “Most neuro-oncology patients trust their physicians to make the best decisions for them, but that does not mean they would accept subtle forms of deception. Patients prefer to have all the information necessary in order to make their own decision.”…”
Section: Translating Nanomedicines To Practicementioning
confidence: 99%
“…In the end the most important thing is that patients are given information necessary to assess therapy options and make informed consent, for example, “Most neuro-oncology patients trust their physicians to make the best decisions for them, but that does not mean they would accept subtle forms of deception. Patients prefer to have all the information necessary in order to make their own decision.”…”
Section: Translating Nanomedicines To Practicementioning
confidence: 99%
“…While ethicists have long been interested in the conflict between these two principles in cases of deception in medical practice, there is comparatively little empirical evidence concerning whether lay people-the potential targets of such deception-regard deception as morally acceptable across different medical contexts. Empirical studies that have been carried out thus far have concerned patient attitudes toward deception in specific medical contexts, such as cancer treatment (Jenkins, Fallowfield, and Saul, 2001;Yu and Bernstein 2011), palliative care, (Fallowfield, Jenkins, and Beveridge 2002), or more generally the use of placebo treatments in medical practice (Chen and Johnson, 2009;Hull et al 2013). Similar studies have also been carried out on physician attitudes toward deception in these contexts (Howick et al 2013;Lyn€ oe, Mattsson, and Sandlund 1993).…”
mentioning
confidence: 99%
“…Similar to patients, caregivers have been found to want proactive, forthcoming, honest and complete disclosure of information regarding medical conditions. 10,11 Previous studies have also reported a desire for information regarding future prognostic implications and associated anticipatory guidance for caregivers, compared to a larger focus on present implications and decision options for patients. 10 Recent efforts to summarize the literature emphasized the importance of proactive information sharing for both patients and caregivers, but yielded knowledge gaps in terms of informational needs pertaining to social, emotional, and spiritual domains for both groups.…”
Section: Papadakos Et Al Informational Needs Of Brain Metastases Patmentioning
confidence: 99%